2012
DOI: 10.5812/ijem.6872
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Leptin During Phases of Menstrual Cycle of Fertile Women: Relationship to Age Groups and Fertility

Abstract: BackgroundIt is established that serum level of leptin is affected by transitional phases of reproduction. It is also reported that the puberty is triggered when body fat and circulating levels of leptin exceed the critical thresholds, butthere is less focus on the serum level of leptin and its relationship with different phases of menstrual cycle and the fertility.ObjectivesThe present study try to determines the serum concentration of leptin and fertility hormonesin the various phases of normal menstrual cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
3
21
0
3
Order By: Relevance
“…This gender by relapse effect is unique and does not appear to be the result of gender-based differences in relapse, which has been found elsewhere (Ward et al 1997) but not in this study. While leptin changes with menstruation have been documented (Ajala et al 2013; Asimakopoulos et al 2009), an equal number of women were in the luteal phase versus the follicular phase during testing and there was no association between menstrual phase and relapse status (al’Absi et al 2015). Other studies of addiction have shown that leptin increases with abstinence from alcohol abuse equally across both genders, though correlations with craving in females but not males has been found in some (Kraus et al 2004) but not all studies (Hillemacher et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This gender by relapse effect is unique and does not appear to be the result of gender-based differences in relapse, which has been found elsewhere (Ward et al 1997) but not in this study. While leptin changes with menstruation have been documented (Ajala et al 2013; Asimakopoulos et al 2009), an equal number of women were in the luteal phase versus the follicular phase during testing and there was no association between menstrual phase and relapse status (al’Absi et al 2015). Other studies of addiction have shown that leptin increases with abstinence from alcohol abuse equally across both genders, though correlations with craving in females but not males has been found in some (Kraus et al 2004) but not all studies (Hillemacher et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen supplementation in ovariectomized female rats restored central leptin sensitivity and reversed body fat redistribution [109]. In humans, serum leptin concentration has been shown to fluctuate during the menstrual cycle in fertile women, peaking at day 14, or at ovulation, like estradiol [110]. Leptin has been shown to regulate ERα and ERβ expression through an ERK signaling pathway in growth zone chondrocytes [111].…”
Section: Pathophysiological Implications Of Membrane Signalingmentioning
confidence: 97%
“…719 The source of luteal phase leptin may be the corpus luteum, which has been shown to produce leptin in humans and in a variety of animals. 3843 Supporting this idea, our study showed lower leptin during the latter half of anovulatory cycles, i.e.…”
Section: Commentsmentioning
confidence: 99%